Juridical Review of Witness Evidence in Criminal Case Trials Who Refuse to Take an Oath - Dewi, Ni Made Cista; Wiratny, Ni Ketut; Damanik, Siti Nurmawan (Westscience Press, 2025)
Witness testimony holds a central position as a valid means of evidence under Article 184 of the Indonesian Criminal Procedure Code (KUHAP). However, the legitimacy of unsworn witness statements remains a contentious legal issue, particularly in cases involving victims of sexual violence, children, or individuals who refuse to take an oath due to psychological, religious, or personal reasons. Articles 160 and 185 of KUHAP mandate an oath as a formal requirement, with limited exceptions under Article 171. The absence of an operational definition for “legitimate reasons” for refusing to swear leads to inconsistent court decisions and legal uncertainty. This research adopts normative, case, and conceptual approaches using secondary data analyzed qualitatively. Findings reveal that most judges strictly interpret the validity of evidence, yet some adopt a progressive stance by accepting unsworn statements as supporting evidence when corroborated by other legal proofs. Reform of criminal procedure law is urgently needed to create a more adaptive system that accommodates substantive justice and the protection of vulnerable witnesses, while ensuring legal certainty and safeguarding human rights in the evidentiary process.